Analisis Kesulitan Membaca Pada Siswa Kelas 2 SD Negeri Rawa - Dini Aprilia Anjani (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2023)
This research was motivated by the low ability of students in early reading in grade 2 of SD Negeri Rawa for the 2022/2023 school year. With this, the purpose of this study is to analyze the initial reading learning difficulties and to find out what factors inhibit the initial reading difficulties of grade 2 students of SD Negeri Rawa. The method used in this study is qualitative descriptive. The subjects of the study were 2 grade 2 students. Data collection techniques using test, observation, interview techniques. The results of the study obtained data from 2 students who were not fluent in reading, including difficulties in recognizing letters, arranging syllables into words, words into sentences. Of these difficulties, there are factors that cause students of SD Negeri Rawa to have difficulty reading, these factors include intellectual factors, namely low levels of student intelligence, psychological namely lack of student interest in reading and family, namely lack of motivation from parents. Based on this understanding, the data concluded that there were 2 students who had difficulty reading including difficulties in recognizing letters, reading syllables, reading words and as for the causative factors, namely intellectual, psychological, and family factors. Keywords: difficulty reading emulation, Elementary School, grade 2